Analysis of students' interest in learning pancasila education in islamic elementary schools - Ali, Aurah Jauhara; Hasanah, Uswatun; Suhendro, Petrus Paulus Mbette (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2025)
One of the main challenges in teaching Pancasila Education at the elementary school level is the low level of student interest in learning. This is reflected in the lack of attention, low engagement, weak internal motivation, and the tendency to procrastinate. In addition, students perceive the subject as boring, even though Pancasila Education is essential for character formation and the development of social skills. This study employed a descriptive qualitative approach with 28 fifth-grade students and one homeroom teacher as participants. Data were collected through observation, interviews, and questionnaires based on Crow and Crow’s learning interest indicators. Triangulation techniques were applied to ensure data accuracy, thus providing a comprehensive overview of students’ learning interest in Pancasila Education. The research findings show that students’ interest in learning Pancasila Education is high when visual media and interactive activities are used. However, their awareness and concentration vary due to lecture-based methods and end-of-day scheduling. The main obstacles include difficulty understanding the material and limited media. Learning interest increases through varied methods, interactive media, differentiation, motivation, and more optimal scheduling. This study contributes by demonstrating that students’ interest in learning civics can be enhanced through a combination of interactive media, varied teaching methods, and differentiation. These findings enrich the discourse on effective strategies that improve students’ motivation, focus, and participation in Pancasila learning.